Synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Materials Chemistry and Physics, 2008)
In the present investigation the synthesis and characterization of high surface area CeO2-doped SnO2 nanomaterial has been reported. The material was synthesized by coprecipitation process combined with surfactant incorporating method. The concentration level of Ce (III) additive was varied systematically from 1 to 11 wt.%. After calcinations at500 degrees C,a high BET surface area of 40 m(2)/g was obtained for 7 wt.% CeO2. The effect of variation of sintering temperature (600-800 degrees C/2h) on the particle size and surface area of a CeO2/SnO2 system was investigated. The material obtained was nanocrystalline, having particle size in the range of 10-16 nm. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: CeO2:SnO2; Nanomaterials; sensors

Synthesis and characterization of high-surface-area Ag2O-doped SnO2 nanomaterial - Gambhire, A. B.; Lande, Machhindra K.; Kalokhe, S. B.; Shirsat, M. D.; Patil, K. R.; Gholap, Ramkrishna S.; Arbad, B. R. (Philosophical Magazine Letters, 2009)
Nanosized tin dioxide-based powders containing silver and palladium oxides have been prepared by coprecipitation reaction. XRD, TEM, and XPS analysis were carried out for investigation of crystalline structure and surface morphology. The best reactive conditions were determined, such as the concentration of the reactants, pH value, surfactants, reaction temperature, and time. The material obtained is nanocrystalline, having a particle size in the range of 5.21-7.42 nm. Effect of doped-Ag2O on the crystal size of the nanoparticles and the influence of the presence of a second dopant (Pd) on the Ag2O/SnO2 matrix was discussed.
Keywords: Ag2O:SnO2; Nanomaterials; XPS